Porcine picobirnavirus infection in Venezuelan farms. - Carruyo Núñez, Gabriela María; Alcalá Aristiguieta, Ana Carolina; Liprandi Fraire, Ferdinando; Ludert Leon, Juan Ernesto (Revista Científica de la Facultad de Ciencias Veterinarias, 2014)
Â Detection frecuency of picobirnaviruses (PBV) genome was evaluated by polyacrylamide gel electrophoresis (PAGE) in 402 piglets faecal samples collected in eight farms from the Central Region of Venezuela. Electrophoretic variability of the genome profile was also evaluated. The presence of PBV and Rotavirus was observed in 50 (12%) and 51 (13%) of the samples, respectively. However, at variance with Rotaviruses, PBV was equally distributed among samples from diarrhoeic and non-diarrhoeic animals. Analysis by electron microscopy of selected positive samples after cesium chloride isopicnic cen- trifugation confirmed the presence of PBV. PBV were found in all age groups tested (7 to 56 days old), and genetic variability was observed among isolates. The genome analysis by PAGE of differents PBV isolates revealed slight variations in the mi- gration patterns for genomic segments 1 and 2. The presence of double or multiple bands in the position corresponding to each genomic segment was also observed, suggesting the co- infection of a single animal with different PBV isolates. Most of the ARN genome segments showed a wide electrophoretic pattern, larger and smaller genome segments ranging from 2.5 to 2.3 and 1.7 and 1.8 kpb, respectively. Narrow electropho- retic profiles were also observed where both bands were lo- cated between rotavirus Ohio State University strain (OSU) segments 4 and 5. Analysis by Reverse Transcription and Po- limerase Chain Reaction (RT-PCR) indicated that these sam- ples were indeed positive for PBV. These results confirm that genetically variable PBV strains circulate frequently in piglets, but their pathogenic potential remains elusive.